The account of distribution of angles of spatial orientation of aircraft at adaptation of radar portraits to varied viewing conditions - S. N. Yarmolik; M. V. Svinarskiy; A. S. Khramenkov; E. V. Zaiko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
A method for estimating and accounting for the statistical distributions of angels for the spatial orientation of an aircraft in the interest of adapting radar systems to changing observation conditions is considered. The influence of the object observation condition on the distribution parameters of the angles of its orientation is analyzed by the method of mathematical modeling. Estimates of the analyzed distribution laws were formed by two methods: the method of statistical test and the Monte-Carlo method. The advantages and disadvantages of each method are considered. The obtained estimates of current distributions of object orientation angles allow adapting radar portraits to changing observation conditions.